Effect of Host Plants on Predator Prey Relationship between Predatory Bug, Orius laevigatus (Fiber) [Hemiptera: Anthocoridae] and Tobacco Whitefly, Bemisia tabaci (Gennadius) [Homoptera: Aleyrodidae] - Abdul-Jalil Hamdan; Iyad Abu-Awad (My University, 2007)
This study was conducted to investigate the effect of host plants on the predatory bug, O. laevigatus. Tobacco whitefly, B. tabaci was offered on tomato and eggplant leaf discs as food source for the predator in the laboratory at temperature of 25±1?C, 75±5% R.H, and 16 L: 8 D photoperiod regime. Results showed that adults of O. laevigatus were able to feed on both eggs and larval instars of B. tabaci maintained either on tomato or eggplant. O. laevigatus preferred significantly (P < 0.05) feeding on B. tabaci eggs more than on larvae. Thus, the average daily consumption of adult O. laevigatus was 30.44 eggs and 3.2 larvae of B. tabaci infesting tomato but that on eggplant was 27.6 eggs and 2.45 larvae. In addition, fertility of O. laevigatus females was significantly greater when the predator fed on B. tabaci reared on tomato than that on eggplant. Thus, the average total nymphs produced by each O. laevigatus female fed on B. tabaci infestation were 64.5 when offered on tomato leaf discs, and 34.8 when offered on Eggplant leaf discs. Therefore, further laboratory and field studies were suggested to be carried out on practical use of O. laevigatus as a biocontrol agent against B. tabaci as a pest.

تم تنفيذ الدراسة الحالية والتي شملت فحوصات مخبرية حول تأثير العوائل النباتية على حياة البق المفترس (O. laevigatus) عند استخدامه عاملا حيويا ضد ذبابة التبغ البيضــاء (B. tabaci) وذلك على كل من نباتات البندورة والباذنجان، تحت ظروف مناخية ثابتة هي درجة حرارة 25±1?C، ورطوبة نسبية 75±5% وفترة إضاءة 16 L: 8 D. تشير النتائج المستخلصة من هذه الدراسة إلى أن الحشرات الكاملة للبق المفترس تمكنت من التغذية على بيوض الذبابة البيضاء ويرقاتها الموجودة على أوراق نباتات البندورة والباذنجان، كما أظهرت حشرات البق أفضلية احصائية في التغذية على بيوض الذبابة البيضاء أكثر من التغذية على يرقاتها. وأن معدل الافتراس اليومي للحشرات الناضجة للبق المفترس كان 30.44 من بيوض الذبابة البيضاء و3.2 من يرقاتها الموجودة على أوراق البندورة، في حين كان معدل الفتراس اليومي 27.6 من بيوض الذبابة البيضاء و 2.45 من يرقاتها الموجودة على أوراق الباذنجان. كما أظهرت النتائج أن معدل خصوبة البق المفترس كانت أعلى إحصائيا عندما قدمت الذبابة البيضاء للبق المفترس على أوراق البندورة منها على أوراق الباذنجان. وأن انثى البق المفترس قد أنجبت ما معدله 64.5 حورية عندما قدمت الذبابة البيضاء للبق المفترس على أوراق البندورة في حين كان معدل اللإنجاب 34.8 عندما قدمت الذبابة البيضاء للبق المفترس على أوراق الباذنجان. وبذلك تظهر النتائج المستخلصة من الدراسة ضرورة إجراء أبحاث مخبرية وحقلية حول إمكانية استخدام حشرة البق المفترس (O. laevigatus)عاملا حيويا لمكافحة حشرة الذبابة البيضاء (B. tabaci)
تأثير العوائل النباتية على علاقة الافتراس ما بين البق المفترس (Orius laevigatus) وذبابة التبغ البيضاء (Bemisia tabaci)